KETERKAITAN ANTARA PERCEIVED QUALITY,KESADARAN MEREK, KESETIAAN MEREK DAN CITRA MEREK - Dedi Hidayah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2011)
As the retail market is still emerging on the last decade, naturally, the competition among players becoming more challenging. Empowering all the resource of the organization as added values would be the strategy to win the targeted market. Brand equity is one of valuable assets of the company since its ability to gain market share against these rivals, and the ability to keep customers by building brand loyalty which can in turn reduce marketingcosts.The purpose of doing this study is to explore the interrelation of four brand equity components; brand awareness, brand loyalty, perceived quality and brand image in modern store industry, and improve the conceptualization of customer-based modern store brand equity.The research design used in this study is the hypotheses testing. The type of relationship between the variables in this study is the co relational research, because the researchers are interested in explaining the important variables related with the problems. The hypothesistesting was done by using Structural Equation Modeling (SEM) with the support of Amos version 7.0.This study is using primary data. The data was collected by questionnaire technique, by giving the written statements to the respondents. And then, the respondents gave their feedback about the statements given. The answers have been available.Keywords: Brand awareness, brand loyalty, perceived quality and brand image